From low-dimensional materials to complex superstructures: A review and outlook - Xu Chao-Fei; Wang Xue-Dong; Liao Liang-Sheng (National Science Open, 2023)
Low-dimensional materials have attracted increasing attention due to their guiding significance for material preparation and potential wide-ranging applications. Through the controllable synthesis and suitably designed fusion of low-dimensional materials into ordered complex superstructures, it has become an effective way to explore new properties of materials and construct structures meeting new application needs. Based on low-dimensional materials such as metal oxides, copolymers, metal-organic complexes, and organic crystals, great efforts have been devoted to the design and construction of complex superstructures with regular repeatability. A series of unique cases including multi-block, core/multi-shell, hyperbranched and network structures have been reported, which has promoted the development of the field of material preparation. Herein, we summarize representative progress of low-dimensional complex superstructures in a reasonable structure classification manner. Ultimately, the existing challenges are discussed, and an outlook is given for future study of precise construction of superstructures as well as exploitation of potential applications.